Got Faith?-An in-depth analysis and review of five faith-based prisoner reentry programs in Florida - Gautam Nayer, Ph.D.*; Luis Perez-Feliciano, Ph.D.; Michael Adams, Ph.D. (The Institute of Academic Research and Publication (IARP), 2021)
In the United States, prisoner reentry programs are a necessity to re-integrate back into society and are of two types: Faith and Non-Faith. With increased emphasis placed on reforming the criminal justice system policies due to Black Lives Matter and other non-profits actively working to change the system from the outside, reentry programs are having a resurgence of interest for effective public policy. There are significant barriers for major policies at the state, local, and federal to be alleviated, nevertheless, our research wanted to consider the effectiveness of five faith-based, male-only reentry programs in central Florida. Small focus groups were utilized to better understand the concerns and issues returning inmates faced in the program as well as when returning to society. Reentry participants were found to have high confidence in the success of their participation in their faith-based program’s efforts on their personal and family growth.